Investigations on real-time charging and discharging pricing of electric vehicles - Muhamad Danish Karlin Bin Mohamed Isa (Nanyang Technological University, 2024)
The increase in electricity demand arising from electric vehicle (EV) charging activities will have an adverse impact on many power grids. With the advent of smart grid technology and the Internet-of-Things (IoT), more sophisticated demand-side management techniques can be explored that allows for more granular control over power delivery to controllable loads, such as EV charging. In this project, an algorithm for the management of routine EV charging activities is proposed. More specifically, the algorithm schedules routine EV charging activities during periods of lower electricity demand on the power grid through the minimisation of spot prices paid to the power grid to prevent the exacerbation of current peak power demand. This algorithm does not require any modification of customer behaviours. This optimised charging scheme is applied in a multi-EV system in MATLAB. The results from this optimisation algorithm are provided to verify the efficacy of the proposed charging scheme.